2009
DOI: 10.1021/es900416h
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Inorganic Carbon Export Across the Soil/Stream Interface and Its Fate in a Boreal Headwater Stream

Abstract: The aim of this investigation was to determine the lateral exportof dissolved inorganic carbon (DIC) from soils of a Swedish boreal forest to a first order stream and to estimate the partitioning of this DIC into CO2 evasion from the stream surface and the DIC pool exported down through the catchment by streamwater. The groundwater entering the stream was supersaturated with CO2 with values as high as 17 times equilibrium with the atmosphere. Up to 90% of the estimated daily soil DIC export to the stream was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
168
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(181 citation statements)
references
References 37 publications
8
168
0
Order By: Relevance
“…4-5). As reported in other studies (Fiedler et al, 2006;Öquist et al, 2009), carbon export rates were mainly determined by discharge, the variations in carbon concentrations and exports being relatively small compared to the flow variation. However, for the whole sampling period, the mean weighted carbon export is almost the same for both DIC (0.9 ± 0.5 mmol m −2 day −1 ) and DOC (0.7 ± 0.7 mmol m −2 day −1 ) (Table 5), and the forest ecosystem exports in total 1.6 ± 0.9 mmol m −2 day −1 (equivalent to 7.0 ± 3.9 g C m −2 yr −1 ), 40 % as DOC and 60 % as DIC (Table 6).…”
Section: Carbon Transfer At the Groundwater-stream-atmosphere Interfacesupporting
confidence: 71%
See 3 more Smart Citations
“…4-5). As reported in other studies (Fiedler et al, 2006;Öquist et al, 2009), carbon export rates were mainly determined by discharge, the variations in carbon concentrations and exports being relatively small compared to the flow variation. However, for the whole sampling period, the mean weighted carbon export is almost the same for both DIC (0.9 ± 0.5 mmol m −2 day −1 ) and DOC (0.7 ± 0.7 mmol m −2 day −1 ) (Table 5), and the forest ecosystem exports in total 1.6 ± 0.9 mmol m −2 day −1 (equivalent to 7.0 ± 3.9 g C m −2 yr −1 ), 40 % as DOC and 60 % as DIC (Table 6).…”
Section: Carbon Transfer At the Groundwater-stream-atmosphere Interfacesupporting
confidence: 71%
“…Spatially, groundwater DOC was on average higher at the mesophyllous to wet Landes station (Bilos and piezometer 3), than at the dry Landes (piezometer 2) during periods with a low water table (Table 4). Indeed, several studies have reported decreasing DOC concentrations in groundwater in concurrence with increasing subsoil thickness and water table depth (Datry et al, 2004;Goldscheider et al, 2006;Pabich et al, 2001), with DOC concentrations at or close to zero reported in deep (> 1 km) and old groundwater (Pabich et al, 2001). At our study site, the fraction of groundwater DOC that predominates at a low water table was probably more recalcitrant, more stabilized and more aged than during high flow.…”
Section: Soil Carbon Leaching To Groundwatermentioning
confidence: 88%
See 2 more Smart Citations
“…However, there was no consistent snow layer in Skogaryd in 2008, so that the impact of the spring melting period was probably negligible. Total inorganic C (TIC) export reported in the literature seems to be of minor importance (< 30 kg C ha −1 yr −1 ; Öquist et al, 2009;Rantakari et al, 2010;Wallin et al, 2010;Dyson et al, 2011). Overall, with reported maxima of 30 and 115 kg C ha −1 yr −1 , the contribution of discharge C losses to the total C budget at Skogaryd is probably low as literature The measured CH 4 flux was very low and always negative; i.e.…”
Section: Potential Losses Due To Dischargementioning
confidence: 82%